Species associated with Curitiba prismatica (D. Legrand) Salywon & Landrum in a Faxinal system - Silva, Richeliel Albert Rodrigues; Watzlawick, Luciano Farinha; Koehler, Henrique Soares; Mazon, Joelmir Augustinho; Leite, Ramon de Sousa (Floresta, 2022)
Species associated with Curitiba prismatica (D. Legrand) Salywon & Landrum in a Faxinal system. Curitiba prismatica, belonging to the family Myrtaceae, is an endemic species of Araucaria mixed forest (AMF) areas whose leaf essential oils have pharmaceutical properties. The objective of this study was to describe the floristic aspects, diversity, competition and diametric transition of the species associated with C. prismatica in an Araucaria mixed forest area exploited in the Faxinal system. A survey of 35 sample units was carried out using the Prodan method, classifying them as initial (pioneer and early secondary) and late (old secondary and climax). Two hundred ten trees were observed, divided into 16 botanical families, 23 genera and 29 species, with the most associated species being: C. prismatica, Casearia oblique, Casearia sylvestris, Cinnamodendron dinisii (30. Ocotea odorifera, and Casearia decandra. The Shannon (H’) and Simpson (C) indices of the associated species were 2.54 nats.ind-1 and 0.14 nats.ind-1, respectively. According to the competition rates denoted by the indices of basal area (BAL), Glover and Hool (IGH) and Hegyi, competition of C. prismatica occurred with greater intensity in trees with DBH ≤ 25 cm. The results provide a better understanding of the ecological behavior of species associated with C. prismatica in AMF areas subject to Faxinal systems.